Production and Characterization of Bio-oil from Bio-mass by Circulating Fluidized Bed Pyrolysis Reactor - Hasan, ATMK; Mohiuddin, M; Ahmed, MB; Poly, IJ; Asadullah, M; Rahman, MS (Bangladesh Journal of Scientific and Industrial Research, 2011)
The objective of the present work is to install a modified suitable and compatible reactor system for the efficient production of renewable liquid fuel (bio-oil) from agro-based bio-mass. This new type of reactor system contains a combustor connected with the upper end of the reactor chamber. The bottom end of the reactor is connected with the bottom part of the combustor by a stainless steel pipe through which hot sand is circulated by the force of air pump. Thus, effective heat transfer from the continuously circulated heated sand as well as efficient biomass conversion into the reactor can be obtained. In this work, jute stick and bagasse abundantly available in Bangladesh were pyrolyzed separately in a continuous feeding circulating fluidized bed reactor at around 500°C for bio-oil production. The total bio-oil yields from bagasse and jute stick were about 69.5 wt% and 68.2 wt% respectively, which are higher than the yields obtained from fixed bed pyrolysis reactor. The total yields of char contents were 19.4 wt% and 21.7wt% after complete pyrolysis of bagasse and jute stick respectively, which are less than that of char yields obtained from fixed bed pyrolysis reactor. Physical and chemical analyses of bio-oils were carried out by conventional methods. The density, viscosity, pH, acid value, water, lignin, solid and ash contents of bio-oils obtained from both jute stick and bagasse were found to be 1.1 g/cc, 3.1 cp, 4.1, 126.3 mgKOH/g, 14.0 wt%, 2.5wt%, 0.05wt%, 0.03wt%, and 1.12 g/cc, 3.2cp, 4.0, 127.1 mgKOH/g, 13.0 wt%, 2.5wt%, 0.015wt%, 0.025wt%, respectively. Key words: Renewable energy; Bio-mass; Bio-oil; Pyrolysis; Fluid bed circulating reactor DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9036 BJSIR 2011; 46(3): 313-322